2020
DOI: 10.1002/1878-0261.12637
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐transmitted circ_MMP2 promotes hepatocellular carcinoma metastasis by upregulating MMP2

Abstract: Exosomes released by tumor cells have been recently identified as important determinants of tumor progression. They often carry circular RNAs that are differentially expressed in tumors and may regulate tumorigenesis and metastasis. Here, we showed that supernatant of 97H hepatocellular carcinoma (HCC) cell line could promote metastasis in L02 human liver cells and HCC cell lines. Moreover, we determined that circ_MMP2 (has_-circ_0039411) could be delivered by 97H-or LM3 cell-derived exosomes to L02 and HepG2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 39 publications
(38 reference statements)
0
59
0
Order By: Relevance
“…With further research on circRNAs, the function and mechanism of circRNAs in malignant tumors have been successively reported 12,13 . For instance, hsa_circ_0005273 serves as a new therapeutic target of metastatic colorectal cancer; 14 exosome-transmitted circ_MMP2 facilitates the metastasis of hepatocellular carcinoma 15 ; circ_AMOTL1 accelerates the growth of cervical cancer by regulating AMOTL1 16 . In our study, we selected "lung cancer" and "circRNA" as the keywords Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With further research on circRNAs, the function and mechanism of circRNAs in malignant tumors have been successively reported 12,13 . For instance, hsa_circ_0005273 serves as a new therapeutic target of metastatic colorectal cancer; 14 exosome-transmitted circ_MMP2 facilitates the metastasis of hepatocellular carcinoma 15 ; circ_AMOTL1 accelerates the growth of cervical cancer by regulating AMOTL1 16 . In our study, we selected "lung cancer" and "circRNA" as the keywords Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate the potential of circRNAs to target host gene 21,22 . Herein, DAB1 is the host gene of circ-DAB1 and best known to regulate the development of neuron migration and lamination 29 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are supported to present high potential to regulate their associated genes 21,22 . Prior works demonstrated that DAB1, the host gene of circ-DAB1, could accelerate chondrogenesis which is another class of differentiation contributing to bone formation 23 .…”
Section: Circ-dab1 Positively Regulates Dab1 Via Inducing Rbpjmentioning
confidence: 99%
“…The high expression of circSHKBP1 in gastric cancer, can be delivered by exosomes and promote the proliferation, migration and invasion of gastric cancer cells in vitro via sponge adsorption of miR-582-3p and binding to HSP90 (111). Exosome-delivered circ_MMP2 in HCC promotes HCC metastasis by up-regulating MMP2 (112). After endothelial cells receive extracellular vesicles (mainly exosomes) carrying circ-CCAC1 released by cholangiocarcinoma cells, circ-CCAC1 can bind to EZH2 in endothelial cells and prevent the nuclear translocation of EZH2, weakening EZH2mediated H3K27me3 modification of SG3GL2 promoter region.…”
Section: Exosomal Circrnas In Gi Tumorsmentioning
confidence: 99%